RECENT DEVELOPMENTS IN NON-INVASIVE PRENATAL DIAGNOSIS AND TESTING. (24th June 2016) - DRURY, SUZANNE; HILL, MELISSA; CHITTY, LYN S
Abstract : The ability to obtain fetal material that could be used for prenatal genetic diagnosis without requirement for an invasive test was a watershed moment in antenatal care. Cell-free fetal DNA (cffDNA) was identified in the maternal plasma by Lo and colleagues in 1997 1 and despite being technically challenging, non-invasive tests for fetal sex determination, fetal rhesus D ( RHD ) genotyping, some single gene disorders and the major aneuploidies are now being offered in clinical practice throughout the world 2 . Progress continues at pace and recent developments in next generation sequencing (NGS) are driving significant advances in research and in the clinical application of non-invasive prenatal testing (NIPT) and diagnosis (NIPD) (Table 1 ).